General Public’s Perspectives on Medical Doctors and Local Clinics in South Korea - Jung, Hyemin (Int J Environ Res Public Health, 2019)
As patients in South Korea play the main role in choosing healthcare providers, understanding their attitudes and beliefs toward medical institutions is essential. This study evaluated the public’s perspectives on doctors and local clinics. A face-to-face interview survey was conducted with 1000 participants who represent the South Korean adult population. The questionnaire consisted of four domains: personal information; trust level for nine professionals, including doctors; healthcare utilization behavior and attitudes regarding local clinics; and assessment of local clinics. The trust level of the doctor was highest (3.16 out of 4) among nine professionals. 85.3% of the participants frequently visited local clinics because of accessibility. The main reason for visiting hospitals over local clinics was the belief that doctors employed at hospitals would be better qualified. People were generally satisfied with the service of local clinics but wanted more facilities and equipment. Among six attributes of primary care, “first contact” and “accessibility” got higher scores in importance and current performance. Lastly, the participants suggested that improving the quality of doctors was most important for the reinforcement of primary care. Efforts to consider public opinion should be made before establishing healthcare policies for primary care.